PENYELESAIAN PERSAMAAN DIFERENSIAL PARSIAL ELIPTIK DIMENSI DUA MENGGUNAKAN METODE ELEMEN HINGGA - , SITI AMINATUR RODHIYAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Partial differential equations are differential equations containing one or more partial differential. Some differential equations may not be solved analytically. In this case, numerical solution are need. Finite element method is one of the numerical method can be used. This final project discussed about second order partial differential equation of two-dimensional elliptic type using finite element method. Its application can be found in heat transfer problem in a steady state. Furthermore, we give the analytic solution of second order partial differential equation of two-dimensional elliptic type for comparing the numeric solution or approach solution with the analytic solution. xvii